2005
DOI: 10.1117/12.605727
|View full text |Cite
|
Sign up to set email alerts
|

Matched filter stochastic background characterization for hyperspectral target detection

Abstract: Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. CAPT WEST JASON E FUNDING NUMBERS PERFORMING ORGANIZATION NAME(S) AND ADDRESS(ES)ROCHESTER INSTITUTE OF TECHNOLOGY PERFORMING ORGANIZATION REPORT NUMBERCI04-1012 SPONSORING/MONITORING AGENCY NAME(S) AND ADDRESS(ES) ABSTRACTAlgo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…The target approach results ( Figure 3 & Results not shown here [6] indicate that this level of performance is not achievable when the man-made targets in the scene are not excluded from computation of the background statistics. Also, the "mixed" background performed particularly well for the high contrast targets indicating that the broader image is well suited to serve as a background, but there was a detrimental impact of including all pixels in the statistics.…”
Section: Training Set Selection By Spatial Subsetmentioning
confidence: 73%
See 3 more Smart Citations
“…The target approach results ( Figure 3 & Results not shown here [6] indicate that this level of performance is not achievable when the man-made targets in the scene are not excluded from computation of the background statistics. Also, the "mixed" background performed particularly well for the high contrast targets indicating that the broader image is well suited to serve as a background, but there was a detrimental impact of including all pixels in the statistics.…”
Section: Training Set Selection By Spatial Subsetmentioning
confidence: 73%
“…If the target exists in the scene (as is the assumption in the target detection problem), then its signature is incorporated in these estimates and the target one is looking for has been explicitly included in the background. This is obviously less significant if the target occupies a very small portion of the image, but it has been shown that including as few as five target pixels in a test set of 18,000 background pixels can alter the eigenvectors of the covariance matrix computed for that test set of pixels [7]. A change in the eigenvectors indicates a change in the shape of the covariance matrix which can dramatically affect the resulting test statistic for detectors based on a Mahalanobis distance (such as the GLRT in equation 3).…”
Section: Background Characterization Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…For instance, anomaly detection attempts to characterize the background and then determine which pixels vary significantly from it (Soofbaf et al 2007, Molero et al 2011. Other detectors use probability distributions and hypothesis testing to identify pixels similar to a target signature that are not the background (Howari 2003, Manolakis et al 2003, West 2005. Commonly used algorithms include spectral angle mapper (SAM), matched filter (in numerous forms), and spectral unmixing (Schaum 2006, Campbell 2007, Schott 2007.…”
Section: Introductionmentioning
confidence: 98%